Human papillomavirus (HPV69/HPV73) coinfection associated with simultaneous squamous cell carcinoma of the anus and presumed lung metastasis (2020)
Background: Human papillomaviruses (HPVs) have been linked to a variety of human cancers. As the landscape of HPV-related neoplasia continues to expand, uncommon and rare HPV genotypes have also started to emerge. Host-virus interplay is recognized as a key driver in HPV carcinogenesis, with host immune status, virus genetic variants and coinfection highly influencing the dynamics of malignant transformation. Immunosuppression and tissue tropism are also known to influence HPV pathogenesis. Methods: Herein, we present a case of a patient who, in the setting of HIV positivity, developed anal squamous cell carcinoma associated with HPV69 and later developed squamous cell carcinoma in the lungs, clinically presumed to be metastatic disease, associated with HPV73. Consensus PCR screening for HPV was performed by real-time PCR amplification of the L1 gene region, amplification of the E6 regions with High-Resolution Melting Curve Analysis followed by Sanger sequencing confirmation and phylogenetic analysis. Results: Sanger sequencing of the consensus PCR amplification product determined that the anal tissue sample was positive for HPV 69, and the lung tissue sample was positive for HPV 73. Conclusions: This case underscores the importance of recognizing the emerging role of these rare 'possibly carcinogenic' HPV types in human carcinogenesis. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.